The weekly law reports 1981 the House of Lords , the Supreme Court of Judicature, Assize Courts, Ecclesiastical Courts, Restrictive Practices Court and National Industrial Relations Court, (Volume1, 1981)
Contain those cases of value to practitioners which are not intended to be included in The Law Reports, together with practice notes and directions